High accuracy theoretical calculation of wavelengths and transition probabilities in Se- through Ga-like ions of tungsten. (May 2018) - Guo, X.L.; Li, M.C.; Zhang, C.Y.; Wang, K.; Li, S.; Chen, Z.B.; Liu, Y.M.; Zhang, H.J.; Hutton, R.; Chen, C.Y.
Highlights: Excitation energies, transition wavelengths, and transition probabilities for the four highly charged tungsten ions from Se-like W 40 + to Ga-like W 43 + are reported. The Multi-configuration Dirac-Hartree-Fock method and the many-body perturbation theory are employed. The most accurate and complete, as of today, atomic data for Se-like through Ga-like tungsten are provided. Abstract: The Ab initio multiconfiguration Dirac-Hartree-Fock (MCDHF) calculations of atomic parameters have been carried out with high accuracy for four highly charged tungsten ions from Se-like W 40 + to Ga-like W 43 + . The second-order relativistic many-body perturbation theory (MBPT) was used to confirm the accuracy of the MCDHF calculations. Excitation energies, wavelengths and transition rates of E1, M1, E2, M2, E3 and lifetimes are presented. The core-valence electron correlation effects arising from deep subshells 3 d and 3 p, have been taken into account along with relativistic effects. The calculated wavelengths are in good agreement with available experimental results.